2007
DOI: 10.1111/j.1600-0404.2007.00907.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hallucinations in Parkinson’s disease using a novel scale

Abstract: TUHARS appears to be a suitable and easily administered instrument for assessment of hallucinations in PD. PD patients experienced various kinds of hallucinations. Hallucinations may have a close relationship with cognitive decline in PD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…Besides, it should be considered that in PD patients with dementia hallucinations may predict a more rapid cognitive decline (Burn et al, 2006). Recently, Wada-Isoe et al (2008) explained that psychotic symptoms represent significant risk factors for institutionalization and for increasing mortality in PD. However, Aarsland et al (2007) reported apathy as the domain more related to caregivers' burden.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, it should be considered that in PD patients with dementia hallucinations may predict a more rapid cognitive decline (Burn et al, 2006). Recently, Wada-Isoe et al (2008) explained that psychotic symptoms represent significant risk factors for institutionalization and for increasing mortality in PD. However, Aarsland et al (2007) reported apathy as the domain more related to caregivers' burden.…”
Section: Resultsmentioning
confidence: 99%
“…However, Fenelon et al (2006) admitted psychotic events as being not only a simple dopaminergic side effect, but also could be part of PD itself, especially in the context of late dementia, depression or mental confusion states. Recently, Wada-Isoe et al (2008) reported that hallucinations occur in the course of dementia itself. Weintraub and Hurtig (2007) considered the pathophysiology of psychosis in PD as a multifactorial phenomenon, involving dopamine replacement therapy and the neurodegenerative process induced by the disease.…”
Section: Resultsmentioning
confidence: 99%
“…Hallucination and psychosis are frequent complications of anti-parkinsonian medications. However, a recent study showed that hallucination may correlate with cognitive decline rather than adverse dopaminergic events [ 34 ]. Other studies suggest that psychosis in PD patients results from multiple etiologies [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although not significant, the PD‐VH group tended to have larger doses of L‐dopa than the PD‐non‐VH group. Previous studies have shown that VH in PD was associated with cognitive impairment, a longer disease duration, and higher L‐dopa levels (Fénelon et al., 2000; Lee et al., 2012; Wada‐Isoe et al., 2008; Zhu et al., 2017). In this study, univariate logistic regression analyses showed that the presence of VH was only significantly associated with MMSE scores and no other clinical characteristics.…”
Section: Discussionmentioning
confidence: 97%